Evaluasi dan Perbaikan Rancangan User Interface pada Website Surabaya Mengaji dengan Menggunakan Metode Design Sprint - Abdillah, Muhammad Azhar; Sagirani, Tri; Kartikasari, Puspita (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2020)
Surabaya Mengaji is a community which included in Islamic Daâ€™wah in surabaya. The one way of daâ€™wah in this community is by the website www.surabayamengaji.com thats release on March 2018. However, by the interview with the website visitors san the managersit found some problems on the display of Surabaya Mengaji website. From the result of the interview, indicates that there is still need to be fixed from the Surabaya Mengaji website. To improve the displayâ€™s problem from Surabaya Mengaji website, the solution is by evaluation and develop User Interface design from the website using Design Sprint Metode. Beside that, it also using the modification from User Experience Questionnaire (UEQ) metode to evaluate the succeed of the website. After doing some analysis, the result is still need to be fixed from the displayâ€™s website. The result of this study are design by user interface which made based from steps on the design sprint metode. The result of the evaluation using UEQ modification concluded that all average value are increased from 2.96 to 3.34. The result of the evaluation which is using UEQ, indicate that the sixths of variabel value are increase and got â€œexcellentâ€ criteria, which is it means that user interface design is made to solve the problems on the website.